The Conductivity Parameters of YBa2Cu3O6.5+ Superconductor Compound - Mohsin, Ali; K. Al-Shakarchi, Emad (Al-Nahrain Journal of Science, 2022)
The high-temperature superconductor like YBa2Cu3O6.5+d was prepared by solid-state reaction method at calcination temperatures (900 °C). The crystal structure was confirmed using X-ray diffraction, and it was found that YBa2Cu3O6.5+d showed orthorhombic phase with lattice parameters (a = 3.82030, b = 3.88548, and c = 11.6835 Å) with space group (Pmmm). The sample was sintered at sintering temperatures (900 °C) for (24 hr). The oxygen excess (d) was nearly (0.36), which was effective in the appearing superconducting properties. The sample YBa2Cu3O6.86 had a critical temperature of about (92 K). The simulation on the XRD-pattern was necessary to predicate the shape of the unit cell and the position of atoms in the unit cell. The last is very important to find some theoretical date, which are benefit in the predication the conductivity parameters through the sequence’s unit cells, which are useful in the conductivity mechanism. This mechanism is depending on the concept of interlayer coupling, so the number of the layers including the unit cell is effective parameter in the conductivity mechanism through the normal resistivity created.